Juan Carlos Moreno García (ed.), From house societies to states: early political organisation, from antiquity to the Middle Ages (Multidisciplinary approaches to ancient societies 3). - Driessen , Jan (Journal of Greek Archaeology, 2024)
The intention behind this volume (and others in the series) is to break compartmental divisions in the study of societies by multidisciplinary comparative approaches. By bringing together a number of chronologically-, culturally- and geographically-diverse focussed papers, the editor succeeds brilliantly in this aim and almost all of the authors have played the game by focussing on aspects of political organisation.